The physical characterisation and composition of archaeological dental calculus - Cooper, Kayleigh Anne (Cranfield University, 2017)
Dental calculus is a complex biological material that has been found to provide significant evidence of past population diet, health and habitual activity. It is composed of mineral phases, trace elements, organic species and can have inclusions such as starch granules and microfossils incorporated into its structure. This composition has been found to vary among individuals, although the reasons for this are poorly understood. Despite this, there is a wealth of knowledge that can be gained from analysing this biomineral, especially from archaeological remains. In past populations, the variables that affect composition, such as pharmaceuticals and diet are reduced compared to modern populations. As such the reliance on clinical studies that have investigated dental calculus from modern individuals, may be flawed when considering past populations. The focus of this study was to provide insight about the variation in physical characterisation and composition of archaeological dental calculus. Despite there being an abundance of archaeological dental calculus research, this is the first large scale compositional study of specimens from three separate past populations. In addition, this research is the first study to adopt a non-destructive to destructive approach to archaeological dental calculus analysis. As well, it is the first application of nanocomputed tomography to dental calculus from past populations. Consequently, this study demonstrates the first evidence of accumulation layering that has been detected using non- estructive nano-computed tomography. Furthermore, this research has identified three types of layering in archaeological dental calculus. Due to these findings, it is expected that this research will impact the future of dental calculus analysis, especially when considering dental calculus as a method of mapping an individual’s health, diet or lifestyle in the weeks or months prior to death. The overall results of this thesis demonstrate that some aspects of the morphological, mineralogical and elemental analysis of archaeological dental calculus are inconsistent with clinical literature. The results have also shown that there are some differences between the dental calculus from different archaeological populations which can be related to post-mortem burial conditions.
Keywords: Forensic anthropology; Dental calculus; Teeth